2022
DOI: 10.1021/acssuschemeng.2c03541
|View full text |Cite
|
Sign up to set email alerts
|

Recyclable, Biobased Photoresins for 3D Printing Through Dynamic Imine Exchange

Abstract: Transimination reactions are highly effective dynamic covalent reactions to enable reprocessability in thermosets, as they can undergo exchange without the need for catalysts, by exposing the materials to external stimuli such as heat. In this work, a series of five biobased vanillin-derived resin formulations consisting of vanillin acrylate with vanillin methacrylate-functionalized Jeffamines were synthesized and 3D-printed using digital light projection (DLP). The resulting thermosets displayed a range of me… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
39
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 46 publications
(53 citation statements)
references
References 58 publications
0
39
0
Order By: Relevance
“…26 Dynamic covalent chemistry has been introduced to FDM filaments, generating products with better isotropic performance. [27][28][29] A variety of polymer designs have been introduced for DIW, producing a plethora of new materials with stimuli-responsiveness, 30,31 outstanding mechanical properties, 32 biocompatibility, 33,34 and optical/electronic properties. 35,36 DIW and vat-polymerization-based 3D-printers are widely used for soft materials AM (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…26 Dynamic covalent chemistry has been introduced to FDM filaments, generating products with better isotropic performance. [27][28][29] A variety of polymer designs have been introduced for DIW, producing a plethora of new materials with stimuli-responsiveness, 30,31 outstanding mechanical properties, 32 biocompatibility, 33,34 and optical/electronic properties. 35,36 DIW and vat-polymerization-based 3D-printers are widely used for soft materials AM (Fig.…”
Section: Introductionmentioning
confidence: 99%
“…Vanillin has grown to become a popular material for bio-based polymers, because of its versatility. 13,14 Soybean oil is another abundant and low-cost bio-based resource with over 50 million tons produced annually. 13,15 Acrylated epoxidized soybean oil (AESO) can be used as a UV curable coating, however it is often blended with petroleum-based monomers due to its limitations with thermal and mechanical properties and poor flowability.…”
Section: Introductionmentioning
confidence: 99%
“…The dynamic linkages are used in conjunction with permanent crosslinks to create materials that retain their shape while self-healing. 14,34,35 The use of DCC in thermosets helps retain the mechanical properties of the networks while gaining the reprocessable properties of a thermoplastic polymer. 14,36 Here we report a series of bio-based and 3D printable CANs that can undergo dynamic transesterification.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In Schiff-base compounds, imines frequently undergo enol-keto tautomerism, which depends on molecular motion ability, proton transfer, and overall crystal packing. Imines also exhibit torsional flexibility and often crystallize in nonplanar geometries, which impacts extended crystal packing. , We recently investigated the solid-state properties of molecules containing one imine group and showed that the torsional flexibility affords unique TE properties . Imine-based molecules have frequently been used as ligands in metal–organic frameworks , and as components within covalent-organic frameworks; however, cocrystals containing imines are less explored . Thus, we were motivated to design and synthesize hydrogen-bonded cocrystals featuring imine functional groups, with the goal of investigating torsional flexibility, dynamic pedal motion, and impacts on TE properties.…”
Section: Introductionmentioning
confidence: 99%